Pancreatic Cancer: Nucleic Acid Drug Discovery and Targeted Therapy - Dai, Hong; Abdullah, Razack; Wu, Xiaoqiu; Li, Fangfei; Ma, Yuan; Lu, Aiping; Zhang, Ge (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic cancer (PC) is one of the most lethal cancers with an almost 10% 5-year survival rate. Because PC is implicated in high heterogeneity, desmoplastic tumor-microenvironment and inefficient drug-penetration, chemotherapeutic strategy currently recommended for the treatment of PC just exerts limited clinical benefit. Nucleic acid-based targeting therapies have become strong competitors in the realm of drug discovery and targeted therapy. A vast of evidence has demonstrated that antibody-based or alternatively aptamer-based strategy largely contributed to the elevated drug accumulation in tumors with reduced systematic cytotoxicity. This review describes the advanced progress of antisense oligonucleotides (ASOs), small interfering RNAs (siRNAs), microRNAs (miRNAs), messenger RNA (mRNAs) and aptamer-drug conjugates (ApDCs) in the treatment of PC, revealing the bright application and development direction in PC therapy.